Flow of pacific water in the western Chukchi Sea: Results from the 2009 RUSALCA expedition. (November 2015) - Pisareva, Maria N.; Pickart, Robert S.; Spall, M.A.; Nobre, C.; Torres, D.J.; Moore, G.W.K.; Whitledge, Terry E.
Abstract: The distribution of water masses and their circulation on the western Chukchi Sea shelf are investigated using shipboard data from the 2009 Russian-American Long Term Census of the Arctic (RUSALCA) program. Eleven hydrographic/velocity transects were occupied during September of that year, including a number of sections in the vicinity of Wrangel Island and Herald canyon, an area with historically few measurements. We focus on four water masses: Alaskan coastal water (ACW), summer Bering Sea water (BSW), Siberian coastal water (SCW), and remnant Pacific winter water (RWW). In some respects the spatial distributions of these water masses were similar to the patterns found in the historical World Ocean Database, but there were significant differences. Most notably, the ACW and BSW were transposed in Bering Strait, and the ACW was diverted from its normal coastal pathway northwestward through Herald Canyon. It is argued that this was the result of atmospheric forcing. September 2009 was characterized by an abnormally deep Aleutian Low and the presence of the Siberian High, which is normally absent this time of year. This resulted in strong northerly winds during the month, and mooring data from the RUSALCA program reveal that the ACW and BSW were transposed in Bering Strait for a significant portion of the month. Using an idealized numerical model we show that the Ekman response to the wind can cause such a transposition, and that the consequences of this will persist on the shelf long after the winds subside. This can explain the anomalous presence of ACW in Herald Canyon during the RUSALCA survey. Highlights: Water masses are tracked through the Russian sector of the Chukchi Sea. Pathways are compared to historical distributions of water properties. Winds in September 2009 were strong due to the Aleutian Low and Siberian High. Water masses were transposed in Bering Strait due to the windforcing.